Dojrzewanie do przyjaźni w roli członka grupy nieformalnej = Growing up to friendship in an informal group - Fudali, Maria (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper is part of research carried out by the author in 2007 in relation to the dynamics of the functioning of informal groups within middle schools. The information obtained from the research regarding group norms biding in informal communities, which include the examined middle schoolers, allowed determining the group member model which they prefer. It can be considered an element of the group`s normative control, determining the behavior of its members, as well as a kind of pass for the candidates, exhibiting character traits preferred in the group.
Keywords: grupa rówieśnicza; gimnazjaliści; przyjaźń